The Effect of Working Capital Financing to the Corporate Performance and the Impact of Financial Constraints in Indonesia Manufacturing Industry - Hansel Winardi; Yosman Bustaman (Conference Series, 2020)
The aim of this research is to gain empirical evidence about the effect of Working Capital Financing to the Corporate Performance of the firms in Jakarta Composite Index (JCI) during the years 2010 – 2018 directly and under the impact of the moderator variable. The moderator variable used Financial Constraints. The Corporate Performance as the dependent variable was calculated by using Return on Assets (ROA) and Tobin’s Q (Q), the Working Capital Financing was calculated by using certain WCF formula, while the Financial Constraints was calculated by using dummy variable that involve some criterias which comprise Firm Size, Cash Flow, and Interest Coverage Ratio. The object of the study is the firms available in JCI in 9 consecutive years and then according to certain aspects. The number of samples should have reliable and qualified financial reports from year 2010 to 2018. Eventually, according to the data analysis and hypothesis testing, this research represented the following results : Working Capital Financing has no significant effect to the Corporate Performance, Working Capital Financing has no significant effect to the Corporate Performance under the Impact of Financial Constraints, Firm Size, Firm Leverage and Firm Growth has significant effect to the Corporate Performance, then Current Ratio has no significant effect to the Corporate Performance.